2007
DOI: 10.1681/asn.2006080862
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Targeting of CX3CL1 (Fractalkine) in Renal Tubular Epithelial Cells

Abstract: The chemokine CX 3 CL1 plays a key role in glomerulonephritis and can act as both chemoattractant and adhesion molecule. CX 3 CL1 also is upregulated in tubulointerstitial injury, but little is known about the subcellular distribution and function of CX 3 CL1 in renal tubular epithelial cells (RTEC). Unexpectedly, it was found that CX 3 CL1 is expressed predominantly on the apical surface of tubular epithelium in human renal transplant biopsy specimens with acute rejection or acute tubular necrosis. For studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…Previous human studies have demonstrated in vivo expression of fractalkine protein by renal tubular epithelial cells. [16][17][18]20 However, we extend these reports by providing in vivo evidence that PTECs, identified on the basis of their expression of aquaporin-1, are a major source of fractalkine in fibrotic kidney disease. Fractalkine expression by human PTECs in vitro has been shown to be induced by protein overload 43 and TNF-a.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous human studies have demonstrated in vivo expression of fractalkine protein by renal tubular epithelial cells. [16][17][18]20 However, we extend these reports by providing in vivo evidence that PTECs, identified on the basis of their expression of aquaporin-1, are a major source of fractalkine in fibrotic kidney disease. Fractalkine expression by human PTECs in vitro has been shown to be induced by protein overload 43 and TNF-a.…”
Section: Discussionmentioning
confidence: 67%
“…19 Expression of fractalkine at tubulointerstitial sites is localized to endothelial cells of the peritubular capillary network and tubular epithelial cells, with cellular infiltrates detected adjacent to fractalkine-expressing tubular epithelial cells. [16][17][18]20 However, the proximal or distal origin of these fractalkine-expressing cells has not been defined.…”
mentioning
confidence: 99%
“…[77][78][79] Fractalkine/CX3CL1 and its receptor CX3CR are upregulated during renal injury in several mouse models, including experimental folic acid nephropathy, crescentic GN, and diabetic nephropathy. 80,81,78,82,83,77,9 Treatment with a neutralizing antibody against fractalkine/CX3CL1 improves renal damage by blocking crescentic formation and macrophage infiltration in rat nephrotoxic nephritis. 84 All these studies imply there might be an important role for CCL and CX3CL chemokines in chronic renal disease regardless of inciting events.…”
Section: Role Of CCL and Cx3cl Chemokines In Chronic Kidney Diseasementioning
confidence: 99%
“…There is evidence that the survival of monocytes and tissue macrophages depends on CX 3 CR1 (31)(32)(33), and this required interaction with cell surface-bound CX 3 CL1 (34). CX 3 CL1 + cells have been shown to be present within glomeruli and in the tubular compartment (35), but their exact identity is unclear.…”
mentioning
confidence: 99%